THE RELATIONSHIP BETWEEN THE LEVEL OF PUBLIC KNOWLEDGE ABOUT ANTIBIOTICS AND THEIR ADHERENCE TO THE USE OF ANTIBIOTICS AT THE SUKOWONO HEALTH CENTER - Mega Cahya Utami (LPPM Universitas dr. Soebandi, 2024)
Antibiotics must be used appropriately. Community non-compliance can be caused by a lack of knowledge about antibiotics. At the Sukowono Health Center, 70% low knowledge, 60% low adherence. The purpose of this study was to find out whether there is a relationship between the level of public knowledge about antibiotics and adherence to the use of antibiotics at the Sukowono Health Center. This study used an analytic observational research method with a cross-sectional approach and used a questionnaire. The total population was 217 and the sample was taken using purposive sampling. It obtained a sample of 140 people who visited the Sukowono Health Center and received antibiotic therapy. Data analysis using Spearman's rank. The results of the research on the level of public knowledge about antibiotics were mostly in the sufficient category (47.1%). While the level of public compliance regarding the use of antibiotics was obtained by the majority (60.7%). Based on the Spearman's rank test, there is a relationship between the level of public knowledge about antibiotics and compliance with the use of antibiotics. The level of knowledge was obtained in the sufficient category, while the level of community adherence to the use of antibiotics was also obtained in the sufficient category. There is a relationship between public knowledge about antibiotics and adherence to the use of antibiotics, the higher the knowledge, the higher the level of adherence. Knowledge is sufficient, compliance is also sufficient, and knowledge is low, compliance is also low. It is expected that health workers will provide detailed information about the impact of inappropriate use of antibiotics. Communities are expected to understand the information provided by health workers.